2014
DOI: 10.2903/j.efsa.2014.3729
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the safety and efficacy of Coxiril® (diclazuril) as a feed additive for turkeys for fattening

Abstract: Coxiril®, containing 0.5 % diclazuril, is intended for the control of coccidiosis in turkeys for fattening at concentrations between 0.8 and 1.2 mg diclazuril/kg complete feed. The highest proposed use level (1.2 mg diclazuril/kg feed) is considered safe for turkeys for fattening. Diclazuril has no substantial antibacterial activity. Diclazuril from Coxiril® is considered toxicologically equivalent to the other currently authorised diclazuril. The use of Coxiril® at the highest proposed use level of 1.2 mg dic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…22 OJ L 266, 7.10.2008, p. 3. 23 OJ L 38, 9.03.2013 The FEEDAP Panel concluded in its opinion on Coxiril ® for turkeys for fattening (EFSA FEEDAP Panel, 2014b) that the highest proposed use level (1.2 mg diclazuril/kg feed) is safe for this major species. None of the endpoints measured in the tolerance study showed a relevant adverse treatmentrelated effect at the 12-fold use level of diclazuril.…”
Section: Safety For the Target Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…22 OJ L 266, 7.10.2008, p. 3. 23 OJ L 38, 9.03.2013 The FEEDAP Panel concluded in its opinion on Coxiril ® for turkeys for fattening (EFSA FEEDAP Panel, 2014b) that the highest proposed use level (1.2 mg diclazuril/kg feed) is safe for this major species. None of the endpoints measured in the tolerance study showed a relevant adverse treatmentrelated effect at the 12-fold use level of diclazuril.…”
Section: Safety For the Target Speciesmentioning
confidence: 99%
“…The efficacy of diclazuril in controlling coccidiosis of chickens for fattening (EFSA FEEDAP Panel, 2014a) and turkeys for fattening (EFSA FEEDAP Panel, 2014b) has been demonstrated at a minimum dose of 0.8 mg/kg complete feed. Considering that the minor species, guinea fowl, is physiologically similar to the major species, chickens for fattening, and that there is some evidence that the effects of diclazuril in Eimeria spp.…”
Section: Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, an opinion on re-evaluation of safety and efficacy of Clinacox ® 0.5 % for chickens reared for laying was adopted in 2013 (EFSA FEEDAP Panel, 2013). EFSA adopted in 2014 three opinions on the safety and efficacy of Coxiril ® (diclazuril) for chickens for fattening (EFSA FEEDAP Panel, 2014a), for turkeys for fattening (EFSA FEEDAP Panel, 2014b) and for guinea fowl (EFSA FEEDAP Panel, 2014c).…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of peroxide oxidation processes in blood plasma was determined by the level of production of its products: primary conjugated dienes (CD) and malonic dialdehyde (MDA) under extraction conditions in a mixture of heptane isopropanol (1:1) as previously described (Gavrilov and Mishkorudnaya, 1983); at wavelengths of 233 and 247 nm; the values of CD expressed as μmol/dm 3 , and MDA at specific absorption rate in 1.0 cm 3 (ΔD/cm 3 ).…”
mentioning
confidence: 99%